Acidibrevibacterium fodinaquatile gen. nov., sp. nov., isolated from acidic mine drainage. Issue 10 (29th July 2019) - Muhadesi, Jiang-Baota; Huang, Ye; Wang, Bao-Jun; Jiang, Cheng-Ying; Liu, Shuang-Jiang
Abstract : A heterotrophic and acidophilic bacterial strain, G45-3 T, was isolated from acidic mine drainage sampled in Fujian Province, PR China. Cells of strain G45-3 T were Gram-stain-negative, non-spore-forming, non-motile and rod-shaped. Catalase and oxidase activities were positive. Strain G45-3 T grew aerobically at 20–45 °C (optimum, 37 °C) and at pH 2.5–5.0 (optimum, pH 4.0). Photosynthetic pigments were not produced. Analysis of 16S rRNA gene sequences showed that strain G45-3 T was phylogenetically related to different members of the family Acetobacteraceae, and the sequence identities to Acidisphaera rubrifaciens JCM 10600 T, Rhodovastum atsumiense G2-11 T and Rhodopila globiformis ATCC 35887 T were 95.9 , 95.3 and 95.3 %, respectively. Strain G45-3 T contained ubiquinone-10 as its respiratory quinone. The major polar lipids were determined to be diphosphatidylglycerol, phosphatidylglycerol, phosphatidylethanolamine, phosphatidylcholine, an unidentified aminophospholipid and an unidentified aminolipid. The predominant fatty acids were cyclo-C19 : 0 ω8 c, C18 : 1 ω7 c, C16 : 0 and C18 : 0 . The genome of G45-3 T consists of one chromosome (3 907 406 bp) and three plasmids (68 344, 45 771 and 16 090 bp), with an average G+C content of 65.9 mol%. Based on the results of phenotypic and genomic analyses, it is concluded that strain G45-3 T represents a novel species of a new genus, for which the name Acidibrevibacterium fodinaquatile gen. nov., sp. nov. is proposed. A. fodinaquatile is nominated as type species and its type strain is G45-3 T (=CGMCC 1.16069 T =KCTC 62275 T ).